(untitled) (Research, Society and Development, 2024)
The dissemination of dubious health information is a challenge for a globalized society. In the academic context, the use of questionable sources can compromise the training of future professionals in the field. Objective: to develop and validate a distance learning course on database research in the health field for undergraduate students. Methodology: a methodological study developed in a higher education health institution, following the instructional design model of Kemp, Morrison and Ross, containing nine stages, allowing the participant to follow a logical sequence of content. The content validation intentionally selected four education specialists, according to adapted Fehring criteria. Consensus was reached in a remote meeting. The semantic validation selected eight undergraduate health students from the same educational institution, for convenience, over the age of eighteen and duly enrolled, also in a remote consensus meeting. Participants were sent a link to the course in advance. Results: A self-instructional distance learning course was designed, with a workload of eight hours, featuring three learning modules: information over time; navigating the main scientific databases; evaluating scientific articles. The structure of the assessments includes two modules with formative assessment and a third module with summative assessment, with at least 70% passing for certification. At the end, a self-assessment of the course was made available. Conclusion: The course is a robust educational product, contributing to quality professional training and promoting the dissemination of good practices in scientific research in the health area.